Redistribution with performance pay - Pawel Doligalski; Abdoulaye Ndiaye; Nicolas Werquin (Federal Reserve Bank of Chicago, 2022)
Half of the jobs in the U.S. feature pay-for-performance. We derive novel incidence and optimum formulas for the overall rate of tax progressivity and the top tax rates on total earnings and bonuses, when such labor contracts arise from moral hazard frictions within firms. Optimal taxes account for the fiscal externalities and welfare consequences of two distinct forces: a direct crowding-out of private insurance and a countervailing crowding-in due to endogenous labor effort responses. These imply that the amount of pre-tax earnings risk to which the worker is exposed is roughly invariant to tax progressivity, whereas the (adverse) welfare consequences of the crowd-out outweigh those of the crowd-in. Quantitatively, the optimal tax policy with performance-pay contracts is close to that prescribed by standard models that treat pre-tax earnings risk as exogenous. Finally, we uncover an efficiency-based argument for taxing bonuses at strictly lower rates than base earnings.
Keywords: 330; moral hazard; performance pay; endogenous wages; optimal taxation; social insurance; bonus taxes; Taxation; Subsidies; and Revenue; Fiscal Policies and Behavior of Economic Agents; Fiscal Policy; Wages; Compensation; and Labor Costs; Compensation and Compensation Methods and Their Effects